Bamboo the amazing grass: a guide to the diversity and study of bamboos in Southeast Asia - Wong, K.M.; International Plant Genetic Resources Institute; University of Malaya (2004)
This joint publication by IPGRI and University of Malaya was mooted as a result of the IPGRI sponsored study on ex situ conservation of bamboo for reference, research and education executed by the Rimba Ilmu Botanic Garden of University of Malaya. The book introduces the bamboos of Southeast Asia, a region well known for its great range of bamboo diversity and utilization. The book discusses the salient aspects of bamboo structure, biology and conservation and provides brief perspectives into the difficult tasks of bamboo classification and identification. A key for identifying the groups and genera of Southeast Asian bamboos that are botanically better known has been provided in the book. This publication also serves as an introduction to the general public and interested professionals to bamboos as a useful plant resource and the multiple facts of bamboo biology, diversity and use. It is a useful publication for general reference to Malaysian and Southeast Asian bamboos.